The average of s, x, and t is (s + x + t)/3. In terms of
y, this equals (2y + 2y)/3 = 4y/3.

Alternatively, you can plug in values for s, x, and t. For
instance, x = 2, t = 4. Therefore, y is 3 and s = 6. The average of the three
numbers would be (2 + 4 + 6)/3 = 4. So when you plug in y equals 3 into the
question, you are looking for an answer that produces 4. Answer: (D).

Related Lessons

There aren't any related lessons for this question. Feel free to use the Help tab to ask our experts if you have questions.